White-lipped peccary (Tayassu pecari, Artiodactyla: Tayassuidae) diet and fruit availability in a Costa Rican rain forest - Mariana, Mariana (2001)
We studied fruit availability, diet and habitat use by white-lipped peccary (Tayassu pecari) in Corcovado National Park, southwest Costa Rica, from July 1996 to April 1997. The results show that the availability of important fruits for the white-lipped peccary differs between habitats and climatic seasons. Fruit availability was highest in the primary forest than secondary and coastal forest. There was a period of shortage of fruits to ends of the wet season, during which the consumption of not seasonal resources like leaves and shafts increased. The important fruits during this period of shortage were Ficus sp and Licania operculipetala. The several types of forest were used according to the fruit availability, and it was a direct relation between the consumption and the fruit availability.